Onion, Potato—Allium cepa L. (Aggregatum group) - James M. Stephens (EDIS)
This document provides an overview of the potato onion (Allium cepa L., Aggregatum group), detailing its characteristics, propagation methods, and cultivation practices. It explains that the potato onion forms clusters of underground bulbs and is typically propagated through bulblets rather than seeds. The document outlines recommended planting times and spacing for Florida, and describes culinary uses for both immature and mature bulbs. Original publication date May 1994.